Wireless algorithms, systems, and applications 6th International Conference, WASA 2011, Chengdu, China, August 11-13, 2011: proceedings - Cheng, Yu (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 6th Annual International Conference on Wireless Algorithms, Systems, and Applications, WASA 2011, held in Chengdu, China, in August 2011. The 26 revised full papers and 13 invited papers presented were carefully reviewed and selected from numerous submissions. The papers address all current trends, challenges, and state of the art solutions related to various issues in wireless networks. Topics of interests include, but not limited to, effective and efficient state-of-the-art algorithm design and analysis, reliable and secure system development and implementations, experimental study and test bed validation, and new application exploration in wireless networks.